A numerical modelling investigation into design variables influencing mixing efficiency in full scale gas stirred ladles - Cloete, Schalk; Eksteen, Jacques; Bradshaw, Steven (Elsevier, 2013)
A mathematical model of a full scale gas stirred ladle was implemented in designed experiments to assess the influence of various design variables on mixing efficiency. The discrete phase (DPM) and volume of fluid (VOF) models were used in conjunction to describe the different phases and the standard k–ε approach was used for modelling turbulence. Ladle height was identified as the most influential factor in determining mixing efficiency and could be altered by either changing the aspect ratio or the overall scale of the ladle. Gas injection through multiple tuyeres was also identified as a promising strategy for improving mixing, but the success of this strategy depended greatly on the tuyere arrangement. Incorrect tuyere arrangements created significant flow pattern interference in the ladle, which had a detrimental effect on mixing. At high aspect ratios, it was shown that the cross sectional area of the ladle can become too narrow, causing additional flow pattern interference between the rising plumes and the downward recirculating flows.